High Current Output Hydrogenated Diamond Triple-Gate MOSFETs - Jiangwei Liu; Hirotaka Ohsato; Bo Da; Yasuo Koide (IEEE Journal of the Electron Devices Society, 2019)
Planar-type and novel triple-gate fin-type hydrogenated diamond (H-diamond) metal-oxide-semiconductor field-effect transistors (MOSFETs) were fabricated on a single-crystalline diamond substrate. The ratio between the height of the lateral side and the width of planar side for each fin of the triple-gate MOSFETs was as high as 1.45. The leakage current densities at an electrical field strength of -1.5 MV cm-1 for both the planar-type and triple-gate fin-type MOSFETs were around 10-6 A cm-2. Both MOSFETs operated well with on/off ratios as high as 1010. The current output maximum normalized by the gate width of the triple-gate H-diamond MOSFET was -271.3 mA mm-1, almost double that of the planar-type MOSFET. The results of this paper are expected to pave the way towards the fabrication of high current out and downscaled H-diamond MOSFETs.